Exploring the spatial architecture of the human dorsolateral prefrontal cortex (DPLFC). - Huamei Li (8815955) (2025)
(A) Clustering spots of DPLFC spatial transcriptomics (ST) data. Clusters are marked by color codes (top). Hematoxylin and eosin (H&E) staining image of DLPFC tissue (bottom). (B) Uniform Manifold Approximation and Projection (UMAP) plot showing the single-cell atlas of human prefrontal cortex. Each dot represents an individual cell. Cell types are marked by color codes. (C) Spatial architectures of DLPFC tissue reconstructed using CellTrek (i), Tangram (ii), and Seurat (iii), respectively. Each dot represents an individual cell. Cell types are marked by color codes. (D) Heat map showing the distribution of cell types in anatomical structures of DLPFC. The intensity of the color indicates the cellular fraction within the specific anatomical region. CellTrek (left); Tangram (middle); Seurat (right). (E) Distribution of selected cell types in DLPFC tissue, reconstructed by different mapping tools. Each dot represents one cell. (F) Bar plot showing the number of cell types effectively mapped to spatial locations. “Reference” represents the total number of cell types in the single-cell atlas of the human prefrontal cortex. The underlying data for this figure can be found at https://zenodo.org/records/17212677. (TIF)